Cardiovascular risk factors in economically disadvantaged women: a study of prevalence and awareness. - Poduri, A. (National Medical Association, 1998)
This study examined the prevalence of cardiovascular risk factors among low-income women and assessed the level of awareness and attitudes about these risk factors in the community. A survey instrument was developed and administered by a single researcher to a convenience sample of women in health clinics and nonclinical community settings. These settings included: an academic clinic, community clinics, women's shelters, free meal sites, community centers, public housing units, and private homes in Philadelphia, Pennsylvania. Two hundred two women were selected without regard to age or race. The mean number of cardiovascular risk factors per subject was 2.6 (SD 1.4). Each of eight established cardiovascular risk factors was identified by 4% to 34% of subjects. Among those women with a specific risk factor, only 0% to 45% reported that they were at increased risk due to the presence of that factor. The prevalence of cardiovascular risk factors among low-income women is substantial. Knowledge and understanding of these risk factors is suboptimal, particularly among women personally affected by risk factors for cardiovascular disease.